Management of Incomplete Microcirculatory Reperfusion After Endovascular Thrombectomy: Focus on Inhibition of the Glycoprotein IIb/IIIa Receptor Pathway - Neeharika Krothapalli; Thomas Ortel; Devin McBride; Adam de Havenon; Lauren H. Sansing; David Hasan; Brian Mac Grory (Stroke: Vascular and Interventional Neurology, 2024)
Endovascular thrombectomy (EVT) is one of the most effective therapies for acute ischemic stroke attributable to large‐vessel occlusion but, despite successful treatment, there remains a significant number of patients with disability. The phenomenon of incomplete microcirculatory reperfusion or no reflow is thought to underlie a substantial proportion of cases with unfavorable outcome. This phenomenon likely arises from platelet aggregation and endothelial edema impacting the cerebral microvasculature, vessels that are below the resolution of digital subtraction angiography. Although incomplete microcirculatory reperfusion prevents tissue recovery and poses a significant clinical challenge, there are multiple therapeutic options administered early after recanalization that have been shown to be promising. In this review, we discuss incomplete microcirculatory reperfusion after EVT and highlight various treatment approaches with a particular focus on antiplatelet therapy, including inhibition of the glycoprotein IIb/IIIa receptor pathway. We also review the rigor of previous studies exploring the use of intravenous and intraarterial administration of tirofiban in neurologic disease before EVT, during EVT, after EVT, or as rescue therapy to determine its effect on clinical outcomes.